Manajemen Pembelajaran Dalam Meningkatkan Prestasi Belajar Siswa - Siti Sofiyah (Cakrawala: Jurnal Kajian Manajemen Pendidikan Islam dan studi sosial, 2022)
This research is based on the importance of character problems in students. In this regard, this study aims to determine the management of character education in moral student realization in SDN 1 Karanggayam. This survey is a qualitative survey. Data collection through interviews, observations and documentation. Validity of data using triangulation. Data analysis techniques include data reduction, data display, and inference drawing. This research led to his five conclusions: (1) Instill in students a sense of values ​​and morality, and aim for character education. These values ​​and morals align with the Madrasa's vision and mission. Instilled character stats include: Religious, sincere, hardworking, smart and caring. (2) The organization of character education, where teachers are role models for madrasah students, is working well. These values ​​and morals are implemented in different ways depending on each teacher's style. (3) Character education leadership includes activities that improve teacher-student relationships, provide students with opportunities to voice their opinions, and motivate students. (4) The control of character education is done by providing students with the development of moral values ​​and literacy. These skills are: Critical thinking, creative thinking, clear communication skills, listening skills, and good moral habits.